The Shedding and Growth Dynamics of Yak Down Wool and Links to Habitat Ecological Conditions - Danzan, Baigalmaa; Tsedev, Khishigjargal; Luvsandorj, Nyambat (Asian Journal of Agriculture and Rural Development, 2014)
This research has been carried out to identify correlations between the shedding and growth dynamics of yak down wool and the ecological conditions of yak habitat. According to the research, the location of the aimags and soums where yak herds are bred in large cold Khangai mountains, with an average altitude of 2000-3300m above sea level. The average winter temperatures dropping to between -300C and -400C and average summer temperature +120C to +200C. In order to survive such harsh environment, the down wool between the coarse top hair fibres grows intensively on yaks at the start of the cold season; throughout winter a yak’s body is covered with down wool with a complete morphological structure consisting of coarse down and mid- type fibres, enabling yaks to withstand cold temperatures. With the onset of spring and warmer temperatures, the hair fibres are gradually shed until June, when new fibres appear. However, the growth of new fibres slows down in the months of July and August, intensifying with the approach of colder months. The research reveals that the adaptive capacity of yaks to the ecological conditions of their habitat affects the renewal process of the morphological structure of yak down.